Microinsurance facilitating risk protection for the poor - Geron, Ma. Piedad S. (2010)
With the development of the microfinance industry (MFI) in the Philippines, MFIs face a growing demand for financial products and services, including risk protection services. Demand for micro-insurance products (i.e., insurance products for the poor) is growing in view of continuing risks to household welfare and the seeming inability of the government to address this issue. The MFIs have realized the need to assist their clients, consisting mostly of poor households and microenterprises, with financial products that will help them manage those risks. A number of those MFIs have started with informal means of risk protection; some have linked up with commercial insurance companies to deliver insurance products to their clientele and still others have established their own mutual benefit associations (MBAs).